2003
DOI: 10.1097/00002030-200305230-00009
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoprotein concentrations relate to the clinical course of HIV viral load in patients undergoing antiretroviral therapy

Abstract: High levels of HDL-cholesterol are associated with a better viral response in treated HIV patients. This association could be related to the sequence similarity and structure homology between apolipoprotein A1 and p17 Gag-HIV protein, which raises the intriguing clinical possibility that inducing an increase in HDL could assist HIV therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 38 publications
3
19
0
1
Order By: Relevance
“…It has been suggested that a strong association between viral replication and both HDL [9,10,12] and host antioxidant defence [33][34][35] exists. The positive relationship between CD4 cell count and PON-1 activity suggests that higher PON-1 activity is associated with a better course of HIV infection and antiviral properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that a strong association between viral replication and both HDL [9,10,12] and host antioxidant defence [33][34][35] exists. The positive relationship between CD4 cell count and PON-1 activity suggests that higher PON-1 activity is associated with a better course of HIV infection and antiviral properties.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, levels of HDL-c have been significantly associated with a better HIV infection course [12]. Furthermore, it has been suggested that, instead of the current practice of only measuring HDL-c values, the evaluation of HDL quality might be an improved tool for identifying subjects at increased risk of cardiovascular events [13].…”
Section: Introductionmentioning
confidence: 99%
“…Low high-density lipoprotein (HDL) cholesterol concentrations are common and characterize dyslipidaemia in patients undergoing long-term antiretroviral therapy [2], resulting in an increased incidence of cardiovascular events [3]. Consequently, clinical laboratories should provide accurate and reliable measurements of HDL cholesterol as part of the continuous management and evaluation of these patients [4].…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggested that cholesterollowering therapy might represent a beneficial strategy for both preventing and treating HIV. Unfortunately, in vivo studies have been discouraging: three studies found no beneficial effect, while two other demonstrated that cholesterol-lowering therapy increased viral replication, particularly in individuals with low cellular cholesterol [4][5][6][7][8]. Furthermore, it was recently found that hypocholesterolemia [total cholesterol b150 mg/dl] was significantly associated with impaired viro-immune response in participants with and without HAART [9].…”
mentioning
confidence: 99%
“…A common view is that adenosine and several other mediators, released during the period of ischemia, play a seminal role in the phenomena, probably being linked to the activation of proliferative signal transduction systems [4]. There are also some theories to explain the development of myocardial stunning, of which the most plausible involve the oxygen paradox, the calcium paradox and the pH paradox [5].…”
mentioning
confidence: 99%